2017
DOI: 10.4172/pharmaceutical-sciences.1000201
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Potential of Green Tea Extract against Experimental Hepatotoxicity in Rats

Abstract: Anudeep, et al.: Green Tea (Camellia sinensis) in HepatotoxicityAn experimental study was conducted to evaluate the hepatoprotective effect of aqueous extract of Camellia sinensis or green tea extract and N-acetyl-L-cysteine in acetaminophen-induced hepatotoxicity in rats. Male Wistar rats (n=24) of 3 mon age were equally divided into 4 groups. Group 1 served as normal control. Hepatotoxicity was induced in the remaining three groups with oral administration of 500 mg/kg of acetaminophen from day 1 to day 3. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…Hepatotoxicity is probably caused by an enzymatic reaction (alcohol dehydrogenase, P450 cytochrome, mitochondrial enzyme), leading to cell damage and interference with biological response systems and metabolic reactions [ 221 ]. Contrary results were reported in rat studies where a green tea extract was shown to have hepatoprotective properties [ 53 , 222 , 223 ]. The antioxidative properties of tea are due primarily to its content of polyphenols, the highest, over 2000 mg in 1000 mL, in white and green tea, and approximately half that in black and red varieties [ 53 ].…”
Section: Tea As An Element Of Prophylaxis and Pharmacotherapy Supplem...contrasting
confidence: 62%
“…Hepatotoxicity is probably caused by an enzymatic reaction (alcohol dehydrogenase, P450 cytochrome, mitochondrial enzyme), leading to cell damage and interference with biological response systems and metabolic reactions [ 221 ]. Contrary results were reported in rat studies where a green tea extract was shown to have hepatoprotective properties [ 53 , 222 , 223 ]. The antioxidative properties of tea are due primarily to its content of polyphenols, the highest, over 2000 mg in 1000 mL, in white and green tea, and approximately half that in black and red varieties [ 53 ].…”
Section: Tea As An Element Of Prophylaxis and Pharmacotherapy Supplem...contrasting
confidence: 62%
“…The destructive ascorbic acid, also called vitamin C (VC), is prominent for applying antioxidant and reducing exercises (Sorice et al, 2014). This investigation demonstrates that green tea extricates control weight actuated liver harm, in any event to a lesser degree, through its cell reinforcement and calming exercises identified with VC (Reddy et al, 2017). Furthermore, VC has been proven to hinder the harm to liver cells (Yang et al, 2018), yet not cholestasis, in rats treated with a solitary ANIT treatment, at any rate to some degree, through its cancer prevention agent and calming exercises (Ohta et al, 2006;Han et al, 2018).…”
Section: Introductionmentioning
confidence: 71%
“…1 Epigallocatechin-3-gallate can also suppress HBV replication and expression by inhibiting HBV promoter transcription and DNA replication, inducing incomplete viral autophagy, and inhibiting chronic pathogenesis. 13 Green tea also has antioxidant and hepatoprotective activities, 14,15 such that it can reverse oxidative stress that may occur due to HBV infection. By capturing free radicals, the balance between redox and cellular antioxidants is maintained, which results in no liver cell damage.…”
Section: Discussionmentioning
confidence: 99%